2022
DOI: 10.3390/hydrology9060099
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the Water Level of Lake Prespa (North Macedonia) Studied by Remote Sensing Methodology: Relation with Hydrology and Agriculture

Abstract: The Ohrid-Prespa lake system is the oldest and most diverse permanent lake system in Europe, dating from the Pliocene era and aged at over 4Ma. Its smaller component is Lake Macro Prespa (thereafter called Prespa), shared by North Macedonia, Albania, and Greece. Lake Prespa’s depth was reported as 14 m mean and 48 m maximum before its major water level decline. The lake is highly sensitive to external impacts, including climate change, and has been suffering major water loss for decades. A lake-level decline o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Additionally, the fact that land cover, and especially agricultural land, has remained stable are converging to the long-term stability of the lake water areas, and thus water contents. The nearest case study examined by similar research was lake Prespa, a transboundary natural lake, located in the borders of Greece, Albania, and Northern Macedonia [ 38 ]. Although lake Prespa is subject to a century-long decrease in water content, it is suggested that increased irrigation of agricultural land has significantly contributed to a more intense rate of water storage loss [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the fact that land cover, and especially agricultural land, has remained stable are converging to the long-term stability of the lake water areas, and thus water contents. The nearest case study examined by similar research was lake Prespa, a transboundary natural lake, located in the borders of Greece, Albania, and Northern Macedonia [ 38 ]. Although lake Prespa is subject to a century-long decrease in water content, it is suggested that increased irrigation of agricultural land has significantly contributed to a more intense rate of water storage loss [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nearest case study examined by similar research was lake Prespa, a transboundary natural lake, located in the borders of Greece, Albania, and Northern Macedonia [ 38 ]. Although lake Prespa is subject to a century-long decrease in water content, it is suggested that increased irrigation of agricultural land has significantly contributed to a more intense rate of water storage loss [ 38 ]. Moreover, another study, examining arid lakes in China, has indicated human uses, and alterations of the basin’s hydrology, as major drivers of lake water loss [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation